Femtosecond Spectroscopy and Quantum Chemistry of a Linearly Coordinated Copper(I) Carbene Complex. Issue 4 (29th December 2022) - Nolden, Oliver; Kremper, Jennifer; Haselbach, Wiebke; Morshedi, Mahbobeh; Guhl, Jasper; Schmeinck, Philipp; Marian, Christel M.; Ganter, Christian; Gilch, Peter
Abstract: Linearly coordinated copper(I) carbene complexes, such as [1, 3‐bis(2, 6‐diisopropylphenyl)imidazol‐2‐ylidene]‐(2‐picoline)copper(I) tetrafluoroborate (1 ), exhibit promising photophysical properties with regard to organic light emitting diode (OLED) applications. Their emission characteristics strongly depend on the surrounding (crystal, matrix, and solution). Here, the behavior of 1 in solution is scrutinized by steady state as well as femtosecond spectroscopy. In coordinating solvents, like acetonitrile and alcohols, 1 is shown to bind solvent molecules as ligands. In non‐coordinating solvents, femtosecond UV/Vis absorption spectroscopy reveals a tri‐exponential decay with time constants of 0.3 ps, 900 ps, and 0.7 μs. The time constants are assigned with the aid of quantum chemistry. A more complex decay is observed in coordinating solvents. Abstract : Solvent effects : The photophysics of a linearly coordinated copper(I) complex was scrutinized using time‐resolved spectroscopy and quantum chemistry. Furthermore, effects of the environment on the structure of the complex are discussed.